Influence of Sprint Duration during Minimal Volume Exercise on Aerobic Capacity and Affect - Haines, Matthew; Broom, David; Stephenson, John; Gillibrand, Warren (International Journal of Sports Medicine, 2020)
The aims of this study were to investigate the influence of reduced-exertion, high-intensity interval training (REHIT), comparing a novel shortened-sprint protocol (SSREHIT) against a traditional protocol (TREHIT), on perceptual responses and to determine if changes in peak oxygen uptake (V˙O2peak) are attenuated with shorter sprints. Twenty-four healthy men undertook 15 sessions of SSREHIT or TREHIT. V˙O2peak was determined at baseline and after completion of each exercise condition. Affective (pleasure-displeasure) responses and perceived exertion were assessed during exercise to capture peak responses. Enjoyment was recorded 5-min after cessation of exercise. Compared to baseline, V˙O2peak increased in both groups (6% for SSREHIT [d=− 0.36] and 9% for TREHIT [d=− 0.53], p=0.01). Affective responses were more favourable for SSREHIT (p=0.001, d=1.62), but both protocols avoided large negative peaks of displeasure. Peak ratings of perceived exertion were lower for SSREHIT (p=0.001, d=− 1.71), although there were no differences in enjoyment (d=0.25). The results demonstrate both exercise conditions can increase V˙O2peak without overly compromising perceptual responses. Decreased sprint duration might further circumvent negative perceptual responses but might also attenuate physiological adaptations.
Keywords: enjoyment; high intensity; interval training; oxygen uptake; perceived exertion; feeling